The toxic influence and biodegradation of carbon nanofibers in freshwater invertebrates of the families Gammaridae, Ephemerellidae, and Chironomidae. (2020) - Chaika, Vladimir; Pikula, Konstantin; Vshivkova, Tatyana; Zakharenko, Alexander; Reva, Galina; Drozdov, Konstantin; Vardavas, Alexander I.; Stivaktakis, Polychronis D.; Nikolouzakis, Taxiarchis K.; Stratidakis, Antonios K.; Kokkinakis, Manolis N.; Kalogeraki, Alexandra; et al.
Graphical abstract: Highlights: Carbon nanofibers had no pronounced pathomorphic effect on freshwater insects. Carbon nanofibers were absorbed in the intestine of freshwater insects. Biodegradation of carbon nanofibers was detected in the digestive tract of insects. Abstract: Carbon nanofibers (CNFs) are widely used in consumer products today. In this study, we assessed the effects of CNFs on the digestive system of three freshwater invertebrate species (Gammaridae, Ephemerellidae, and Chironomidae). The aquatic insects Diamesa sp., Drunella cryptomeria, and Gammarus suifunensis were incubated with the CNFs at the concentration of 100 mg/L during the 7-days period. Histological examination of the whole specimens and the longitudinal sections revealed no toxic effects of CNFs. However, a noticeable change in the structure of the CNFs accumulated in the intestines of the aquatic insects was found by Raman spectroscopy. The registered decrease in the relative proportion of amorphous carbon included in the CNF sample was found in the intestines of Diamesa sp. and D. cryptomeria . The registered effect can indicate a biodegradation of amorphous carbon in the digestive tract of these two insect species. In contrast, the decrease of highly structured carbons and the decrease of G-bonds intensity were registered in the digestive tract of G. suifunensis . This observation demonstrates the partial biodegradation of CNFs in the digestive tract of G. suifunensis .